Implementation of the Balanced Scorecard for Performance Evaluation at Universitas Prima Indonesia - Nazli Fahada; Tien Rafida; Muhammad Fadhli (CV. Creative Tugu Pena, 2026)
This study aims to analyze the implementation of the Balanced Scorecard (BSC) in evaluating the performance of Universitas Prima Indonesia (UNPRI) as one of the leading private universities in North Sumatra. The Balanced Scorecard approach is selected because it provides a comprehensive overview of organizational performance through four main perspectives: financial, customer, internal business processes, and learning and growth. This research employs a qualitative approach. Data were collected through interviews, observations, and analysis of institutional documents related to financial management, human resources, academic services, and institutional development. The data were analyzed using a descriptive-analytical technique to illustrate the actual condition of the university’s performance based on the four perspectives of the Balanced Scorecard. The findings indicate that the implementation of the Balanced Scorecard at Universitas Prima Indonesia has supported a more structured and strategic performance evaluation. The financial perspective shows relatively effective resource management in supporting institutional sustainability. The customer perspective reflects a high level of satisfaction among students and stakeholders regarding educational services. From the internal business process perspective, UNPRI demonstrates a systematic governance and quality assurance system. Meanwhile, the learning and growth perspective reveals a strong commitment to developing the competencies of lecturers, staff, and students. This study provides both theoretical and practical contributions to the development of a Balanced Scorecard-based performance evaluation model in higher education. It can also serve as a strategic reference for other universities in improving institutional performance and competitiveness in a sustainable manner.